Magnetic resonance imaging assessment of the therapeutic effect of combined electroacupuncture and stem cells in acute peripheral nerve injury - Chen, Yueyao; Pan, Zhongxian; Meng, Fanqi; Yu, Xuewen; Xu, Qian; Huang, Leyu; Liang, Qiumei; Wu, Yanglei; Lin, Xiaofeng (Frontiers in Cellular Neuroscience, 2022)
Objectives: This study aimed to evaluate the therapeutic effect of a combination of Bone Mesenchymal stem cells (BMSCs) transplantation and Electroacupuncture (EA) for acute sciatic nerve injury in rats using magnetic resonance. Methods: Ninety-two male adult healthy Sprague-Dawley rats were randomly divided into the EA+BMSCs group, EA group, MSCs group, and PBS group (control). Electroacupuncture was performed on a rat receiving EA treatment at Huantiao (GB30) and Zusanli (ST36). T2 values and diffusion tensor imaging (DTI) derived from multiparametric magnetic resonance imaging (MRI), histological assessments, and immunohistochemistry was used to monitor nerve regeneration. Walking track analysis was used to assess nerve functional recovery. Repeated-measures one-way analysis of variance was used to evaluate the significance of T2, DTI, and SFI values among the four groups. One-way analysis of variance was used for comparing the histological characteristics. Bonferroni test was used for multiple pairwise comparisons at each time point. Results: In terms of FA, the EA+BMSCs and EA groups had faster recovery than PBS (control) in all time points after surgery, and the EA+BMSCs group recovered better than the BMSCs group at 3 weeks (P ≤ 0.008). FA values were higher in the EA group than in the BMSCs group at 4 weeks (P ≤ 0.008). In terms of RD, the EA+BMSCs group recovered better than the BMSCs group at 2 and 4 weeks (P ≤ 0.008). Immunofluorescence staining for axon guidance molecule netrin-1 revealed that it was significantly higher in the EA+BMSCs subgroup and EA subgroup than it was in the control (PBS) subgroup at 1–3 weeks (P < 0.001). Immunofluorescence staining for S100 showed the continuity of nerve fibers recovered more quickly in the EA+BMSCs subgroup than in the BMSCs subgroup. Conclusion: Our research revealed that a combination of MSCs and EA can provide both topological and biomolecular guidance to promote axonal extension, myelin regeneration, and functional recovery after PNI. EA not only promotes nerve repair on its own, but also enhanced the beneficial effects of stem cell treatment and the secretion of netrin 1, a guidance regeneration factor, and promotes the orderly growth of nerve fibers. These PNI repairs could be monitored non-invasively and in situ by MRI. The FA and RD values derived from MRI could be sensitive biomarkers to reflect the PNI repair process.